Effect of Hemodialysis on Glaucoma Patients - Hendricks TM; Quist TS; Wang K; Antes LM; Boese EA (Clinical Ophthalmology)
Tina M Hendricks,1 Tyler S Quist,1 Kai Wang,2 Lisa M Antes,3 Erin A Boese1 1Department of Ophthalmology and Visual Sciences, Carver College of Medicine, University of Iowa, Iowa City, IA, USA; 2Department of Statistics, Carver College of Medicine, University of Iowa, Iowa City, IA, USA; 3Department of Internal Medicine, Carver College of Medicine, University of Iowa, Iowa City, IA, USACorrespondence: Erin A Boese, Department of Ophthalmology and Visual Sciences, University of Iowa, 200 hawkins Drive, Iowa City, IA, 52242, USA, Tel +1 319 356 3938, Fax +1 319 353 7699, Email erin-boese@uiowa.eduPurpose: Prospective study to determine if patients with glaucoma are at increased risk of intraocular pressure (IOP) fluctuation and changes in ocular perfusion pressure (OPP) during hemodialysis (HD) sessions when compared to patients without glaucoma.Patients and Methods: Patients undergoing HD at the University of Iowa for end-stage renal disease were recruited. Enrollment was restricted to patients undergoing standard HD sessions for a minimum of three months. Hand-held slit lamp examination, IOP, blood pressure (BP), and central corneal thickness (CCT) measures were taken at the following three time points: the beginning of the session (before), at the half-way point (middle), and at the conclusion of the session (end). Ocular perfusion pressure was calculated using the formula: 2/3[diastolic BP + 1/3 (systolic BP – diastolic BP)] – IOP.Results: Every eligible patient having dialysis was approached, and 105 eyes of 54 patients were recruited for the study. The glaucoma cohort included 19 eyes from 11 patients. The variability in IOP from the beginning to the end of HD (end-before) was 1.54 mmHg greater in the glaucoma group (p=0.005), with some glaucoma patients having IOP increases up to 25 mmHg. Ocular perfusion pressure decreased significantly more in glaucoma patients compared to controls at both middle-before (p=0.008), and end-before (p=0.01) time points.Conclusion: Glaucoma patients may be more vulnerable to IOP swings and drops in OPP during HD sessions compared to controls. In all cases, these changes were asymptomatic, potentially placing glaucoma patients at increased risk for glaucomatous progression during each HD session. Our results suggest that HD may be an independent risk factor for glaucomatous progression, and may be especially worth investigating in patients with progression despite low to normal IOPs measured in clinic.Keywords: ocular perfusion pressure, hemodialysis, dialysis, intraocular pressure fluctuation, glaucoma